Cushing's syndrome associated with recurrent endometrioid adenocarcinoma of the ovary. Issue 8 (August 1994) - Crawford, S M; Pyrah, R D; Ismail, S M
Abstract : Ectopic production of adrenocorticotrophic hormone (ACTH) by malignant neoplasms is a well recognised cause of Cushing's syndrome but is extremely rare in ovarian carcinoma. A patient who underwent surgery for ovarian carcinoma followed by a course of chemotherapy is reported. The tumour was a bilateral moderately differentiated endometrioid adenocarcinoma and contained numerous chromogranin immunoreactive endocrine cells as well as small foci of ACTH immunoreactivity. She subsequently presented with Cushing's syndrome in association with extensive pelvic recurrence of the tumour.